Product selectivity of photocatalytic CO2 reduction reactions. (January 2020) - Fu, Junwei; Jiang, Kexin; Qiu, Xiaoqing; Yu, Jiaguo; Liu, Min
Graphical abstract: Abstract: Photocatalytic carbon dioxide (CO2 ) reduction to obtain hydrocarbon solar fuels is one of the promising strategies to solve energy crisis and complement carbon cycle. However, the low activity and poor product selectivity greatly limit its practical application. Tuning product selectivity is of great significance to improve the yield of target product and deepen the understanding of CO2 reduction reaction mechanism. In this review, we firstly summarize the widely accepted pathways of photocatalytic CO2 reduction reactions. Secondly, important factors affecting product selectivity are analyzed, mainly including light-excitation attributes, band structure of photocatalysts, separation of photogenerated charge carriers, adsorption/activation of reactants, surface active sites of catalytic reaction, and adsorption/desorption of intermediates. Finally, the challenges and perspectives in developing photocatalysts with high CO2 reduction efficiency and product selectivity are presented.